1957
DOI: 10.1002/jsfa.2740080207
|View full text |Cite
|
Sign up to set email alerts
|

The destruction of vitamin e in flour by chlorine dioxide

Abstract: Chemical estimations of the tocopherols present in wheaten flours treated with chlorine dioxide, or untreated, have been made by a method which allows the separation of the different forms of the vitamin. The chlorine dioxide caused almost complete destruction of each of the tocopherols. Biological tests demonstrated that untreated flour, when included as the main component of the diet of rats, contains enough tocopherol to satisfy their requirements. Rats developed various signs of avitaminosis E, however, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1958
1958
2011
2011

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…For adults, the consumption of wheat is mainly from bread. Some researchers (Menger, 1957;Moore et al, 1957;Slover and Lehmann, 1972;Piironen et al, 1987) have reported losses of vitamin E between 5 and 50% during breadmaking. Most of those studies were performed 20 or more years ago using other than current methods of vitamin E analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For adults, the consumption of wheat is mainly from bread. Some researchers (Menger, 1957;Moore et al, 1957;Slover and Lehmann, 1972;Piironen et al, 1987) have reported losses of vitamin E between 5 and 50% during breadmaking. Most of those studies were performed 20 or more years ago using other than current methods of vitamin E analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it has been clearly proved, by both chemical and biological methods, that even treatment with chlorine dioxide at about the ordinary commercial level causes almost complete destruction of the vitamin E which is naturally present in the flour McDermott, 1953, 1954;Frazer, Hickman, Sammons, and Sharratt, 1956a;Moore, Sharman, andWard, 1957, 1958). Another indication of injury to the flour, apparently distinct from the destruction of vitamin E, may perhaps be seen in the results of feeding-trials with successive generations of rats by Frazer, Hickman, Sammons, and Sharratt (1956b).…”
Section: Discussionmentioning
confidence: 99%
“…However it is this degree of deficiency which is commonly studied in experimental animals. I n man it is subdeficiency particularly which should be detected and investigated because industrial and cooking processes tend to destroy tocopherols in many foodstuffs (Moore, Sharman & Ward, 1957;Kelleher & Losowsky, 1970;Smith, Kelleher, Losowsky & Morrish, 1971). Jager (1973) has suggcsted that a high percentage of human beings may be instances of bordcr-line vitamin E deficiency.…”
Section: (4)mentioning
confidence: 99%